Analisis Model Produksi Berita Televisi Lokal: Studi TVRI Stasiun Penyiaran Kalimantan Selatan dan Banjar TV - Hesti Dwi Yulianti; Masduki Masduki (Jurnal Komunikasi, 2008)
News program in local television has its own charm for the local civilization more than the news program in the national television. Local Banjarmasin news program, also challenged by another private television station whom broadcasting its program nationally. In order to strengthening its power in competition, TVRI Stasiun Penyiaran Kalimantan Selatan and Banjar TV as a station who have an interesting program have to use what they have in local area. This research has found some discoveries. First, the production process of local news with the material to cover an event start from the idea planning, job distribution and equipment check were done as the standard procedure in broadcasting. Second, production stage, live or recorded, can be executed due to the station decision and the will of corporate management. Any kind of program, live and recorded, should be processed carefully and involving all crew in charge. Third, both of the television station adopted local value within the program, religious theme, cultural outfit, cultural song and also adopted cultural symbol which is shown in the news production process.